Effectiveness of a Cognitive Behavioral Therapy Counseling Approach in Overcoming Online Game Addiction - Wina Mariana; Ali Daud Hasibuan (Universitas Muhammadiyah Enrekang, 2024)
Abstrak Addiction to online games is a problem in the world of education which can have various negative impacts on students, both physical, psychological and social health, as well as learning activities and even a decline in academic achievement. This research aims to determine the effectiveness of the cognitive behavioral counseling approach in alleviating online game addiction experienced by students. The research method uses a quantitative comparative type with a 2 x 2 factorial quasi-experimental design. Samples were taken using a purposive technique of 10 people in the experimental group and 10 people in the control group. The research instrument used an online game addiction scale which was distributed to the sample during the pretest and posttest. The data analysis technique uses data description and hypothesis testing with the ANACOVA formula. The research results showed that there was a difference in students' online game addiction scores during the pretest and during the posttest with an F value of 417.217, and a mean square of 544.700 with a significance of 0.000. It can be concluded that counseling services using the Cognitive Behavior Therapy approach are effective in reducing online game addiction in students at Tritech Vocational School, Medan. Keywords: CBT, Games, Addiction. Abstract Addiction to online games is a problem in the world of education which can have various negative impacts on students, both physical, psychological and social health, as well as learning activities and even a decline in academic achievement. This research aims to determine the effectiveness of the cognitive behavioral counseling approach in alleviating online game addiction experienced by students. The research method uses a quantitative comparative type with a 2 x 2 factorial quasi-experimental design. Samples were taken using a purposive technique of 10 people in the experimental group and 10 people in the control group. The research instrument used an online game addiction scale which was distributed to the sample during the pretest and posttest. The data analysis technique uses data description and hypothesis testing with the ANACOVA formula. The research results showed that there was a difference in students' online game addiction scores during the pretest and during the posttest with an F value of 417.217, and a mean square of 544.700 with a significance of 0.000. It can be concluded that counseling services using the Cognitive Behavior Therapy approach are effective in reducing online game addiction in students at Tritech Vocational School, Medan. Keywords: CBT, Games, Addiction.